Cervical Cytology and HPV Genotype Type 16 and 18 Infection in Female Commercial Sex Workers in Makassar - Joko Saputro, Sulystyawan; Arifuddin, Sharvianty; Soraya Riu, Deviana; Sunarno, Isharyah; Rauf, Syahrul; B. Farid, Retno (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to determine the cytology and type of human papilloma virus (HPV) in commercial female sex workers in Makassar. This descriptive study was performed on cervical fluid samples from 80 female sex workers. The cytological examination was performed using the Thin Prep Pap Test and the DNA HPV detection (genotyping) using the reverse dot blot "flow through" hybridization method. In this research, most of the female commercial sex workers in Makassar have non-specific cervicitis. Non-specific cervicitis was present in 48 (60%) samples and negative lesions in 32 (40%) samples. HPV DNA testing (HPV genotyping) shows that the prevalence of high-risk HPV types 16 and 18 in this study was low; HPV type 16 was only found in 5 samples, whereas type 18 was absent. The proportion between high-risk HPV (other than types 16 and 18) and low-risk is comparable.